2018
DOI: 10.3201/eid2408.180280
|View full text |Cite
|
Sign up to set email alerts
|

Ancylostoma ceylanicum Hookworm in Myanmar Refugees, Thailand, 2012–2015

Abstract: This hookworm, uncommonly found in humans, has a higher cure rate than that for Necator americanus hookworm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…A study by O'Connell et al on Myanmar refugees living in Thailand found a baseline prevalence of 5.4% for An. ceylanicum [44]. Hookworm species cannot be differentiated under the microscope, so it is likely that many studies have been including An.…”
Section: Diagnostic Sensitivity and Methodology Testingmentioning
confidence: 99%
“…A study by O'Connell et al on Myanmar refugees living in Thailand found a baseline prevalence of 5.4% for An. ceylanicum [44]. Hookworm species cannot be differentiated under the microscope, so it is likely that many studies have been including An.…”
Section: Diagnostic Sensitivity and Methodology Testingmentioning
confidence: 99%
“…Previously, we described a pipeline for the identification of high-copy number repetitive DNA elements for use as semi-quantitative real-time PCR (qPCR) targets for the detection of various STH species [2021]. These targets, identified utilizing next-generation sequencing (NGS)-based analysis tools, have facilitated improved sensitivity and specificity of detection, leading to their adoption in various diagnostic efforts and operational research (OR) studies such as the DeWorm3 cluster randomized trials [11, 14, 22]. Despite the availability of such tools, to date, the qPCR-based detection of A .…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostics based on targets discovered using this technique have proven useful in both past and ongoing field tests in Kenya (Pickering et al, 2019), Bangladesh (Benjamin-Chung et al, 2019), Ethiopia, Uganda, Timor Leste (Papaiakovou et al, 2017), Thailand (O’Connell et al, 2018), Liberia (Fischer et al, 2018), Japan, Benin, Malawi, India, and the Southern US, and have been adopted for use by large operational research efforts, such as the DeWorm3 cluster randomized trials (Ásbjörnsdóttir et al, 2018). However, testing biological samples, whether for diagnosing individuals or getting an overview of the epidemiological environment of a region, involves a myriad of factors, such as unexpected or emerging parasites, zoonotic infections, and misleading material in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar case, the same ITS-based primer set (Llewellyn et al, 2016) was used to investigate Ancylostoma duodenale in a field study of a refugee population in Thailand (O’Connell et al, 2018). Since the most common human Ancylostoma parasite is A. duodenale , the results were initially believed to indicate A. duodenale infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation